Effect of celery (Apium graveolens) extract on the growth, haematology, immune response and digestive enzyme activity of common carp (Cyprinus carpio) - ALİ MOHAMED, Gamaia; DAW AMHAMED, İman; ALHADİ ALMABROK, Ahmed; B. ALİ BARKA, Abobaker; BİLEN, Soner; ELBESHTİ, Randa Tahir (Marine Science and Technology Bulletin, 2018)
In this study, the effect of a dietary supplementation of Apium graveolens on growth performance, digestive enzyme activities and immune response of juvenile common carp (Cyprinus carpio) were evaluated. C. carpio, with an average weight at the beginning of the experiment of 6.5 ± 0.07 g, were supplemented with a celery (Apium graveolens) aqueous methanolic extract at a dose of 0% (control), 0.1%, 0.5% or 1% over 45 days. Every 15 days, respiratory burst, lysozyme and myeloperoxidase activity were measured, and at the end of the study, haematological responses, growth performance and digestive enzyme activity were investigated. Respiratory burst and myeloperoxidase activity was significantly improved in all treated groups compared with the control group (P ˂ 0.05). Lysozyme activity was highest in the 0.1% and 1% extract groups. At the end of the study, the final weight (FW), weight gain (WG) and specific growth rate (SGR) were significantly increased in the 0.1% group compared with the other groups. The feed concentration ratio was decreased in the 0.1% and 1% groups compared with the control (P < 0.05). Haematological parameters were affected by A. graveolens extract intake (P ˂ 0.05). The total white and red blood counts, haemoglobin content and haematocrit value were highest in the 0.1% extract group (P ˂ 0.05). However, the mean cell volume and mean cell haemoglobin concentration were decreased in the 0.5% group (P ˂ 0.05). Digestive enzyme activity (trypsin, amylase and lipase) in all experimental groups was significantly elevated compared with the control (P ˂ 0.05). These results indicated an immunostimulatory and growth-promoting effect and increasing digestive enzyme activity of C. carpio supplemented with an A. graveolens aqueous methanolic extract.
Keywords: Hidrobiyoloji; Naval Science; V; growth; Naval architecture. Shipbuilding. Marine engineering; SH1-691; VM1-989; A. graveolens; Common carp; Growth; Haematology; Immune response; Digestive enzymes activity; immune response; common carp; a. graveolens; haematology; Aquaculture. Fisheries. Angling; digestive enzymes activity; Hydrobiology; 3. Good health